Association Between Functional and Structural Brain Connectivity of the Default Mode Network in Non-treatment Seeking Individuals With Alcohol Use Disorder. (21st December 2021) - Gerhardt, Sarah; Karl, Damian; Mann, Karl; Kiefer, Falk; Vollstädt-Klein, Sabine
Abstract: Aims: Alcohol use disorder (AUD) is associated with alterations within the default mode network (DMN) at rest. Also, impaired white matter structures have been observed in individuals with AUD. This study developed a workflow for examining the relation between functional and structural connectivity, exemplary for nodes of the DMN within a sample of non-treatment seeking individuals with AUD. Furthermore, AUD severity was correlated with both measures independently. Methods: The functional magnetic resonance imaging (fMRI) protocol included anatomical, resting state and diffusion weighted imaging measurements. Independent component analyses and deterministic fiber tracking as well as correlation analyses, including the severity of AUD, were performed. N = 18 out of 23 adult study participants took part in the fMRI examination, and N = 15 were included in the final analyses. Results: Established resting-state networks were reliably identified in our sample. Structural connections were found between several nodes of the DMN, whereas only fibers between the medial prefrontal cortex and the posterior cingulate cortex were reliably detected in all individuals. A negative correlation was observed between brain activation during rest and AUD severity in left parietal and temporal regions and the putamen. A more severe AUD predicted impairments in white matter integrity of the cingulum. Conclusion: In AUD, information obtained from a combination of resting-state, diffusion weighted data and clinical information has great potential to provide a more profound understanding of the disorder since alterations may already become apparent at earlier stages of the disorder, e.g. in non-treatment seeking individuals. Summary: Alcohol use disorder leads to alterations in the default mode network of the resting brain that is associated with the severity of the disorder. Following our workflow, white matter impairments can be observed between some of the nodes of the default mode network using diffusion tensor imaging. Both, resting-state functional and structural connectivity relate to the severity of alcohol use disorder.